The Organizational Effectiveness in Community Colleges in Light of The Pounder Model: A Field Study in The Kingdom of Saudi Arabia in 1443 AH - Al-Hoshan, Amal Hoshan (Journal of Educational and Psychological Sciences, 2023)
The study aimed to measure organizational effectiveness of Saudi community colleges in the light of the dimensions of the Pounder model (1999) from the point of view of faculty members in community colleges in Saudi universities. To achieve the objectives of the study, the descriptive survey method was used, as well as the questionnaire as a tool for the study, which consisted of (32) phrases divided into four axes, and was applied to a simple random sample of (228) members of the study community, which included all faculty members in community colleges in (4) public universities, totaling (475). The study found that the most prominent results of the reality of the organizational effectiveness of community colleges in Saudi universities were represented in the dimension of planning and setting goals with an average of (3.76 out of 5), followed by the dimension of information and communication management with a mean of (3.54), followed by the dimension of productivity and efficiency with an average of 3. (3.49), and finally the integration dimension came with an arithmetic mean (3.25). The study recommended that community colleges pay attention to achieving internal and external integration to improve their organizational effectiveness. Internal integration is represented in taking care of the interests of the various stakeholders within the college, including students, faculty members and administrative staff, in addition to to achieving integration with the local communities that it serves, whether individuals or organizations.
Keywords: organizational effectiveness, goal model; system model; CVM; Pounder model (1999); higher education; community colleges